Analysis Of Factors That Influence Pregnant Woman Behavior In Doing Laboratory Examination In Sumberpucung Of Public Health - Asri Dewi Wahyuningtyas (Journal for Quality in Public Health, 2020)
The low laboratory examination in pregnant women is influenced by several factors, one of which is family support, the role of health and distance with health services. The purpose of this study was to determine the effect of family support factors, the role of health workers, and the distance to laboratory examination behavior in pregnant women. Sumberpucung Health Center. This research design is correlation analytic. The population in this study were all pregnant women in Puskesmas Sumbepucung amounted to 140 large sample of 104 respondents with a sampling technique that is Simple Random Sampling. The independent variable is family support, the role of health workers, and distance of health services while the dependent variable is the behavior of laboratory examinations. The test used is linear regression. Based on the analysis using the statistical test of linear regression obtained p value of family support of 0.01, because ρ-value <0.05 then H0 is rejected, and H1 is accepted, which means there is an influence of family support for behavior while for the role of health workers is obtained p value 0.846 and for a distance of p value 0.664 so that there is no influence of the role of health workers and distance on behavior. Family relationship is the most influential factor in laboratory examination behavior. Family support is a psychosocial support that is able to provide emotional strength to the mother. Family affection by providing support to pregnant women can provide motivation for mothers so that mothers conduct laboratory examinations